LEARNING TO TEACH L2 PRONUNCIATION VIA ONLINE AND BLENDED ON-CAMPUS COURSEWORK - Amanda Baker; Michael Burri (TEFLIN Journal, 2025)
This article focuses on the preparation of second language (L2) teachers in a Teaching English to Speakers of Other Languages (TESOL) program offered in Australia. Specifically, it explores the learning development of student teachers in learning how to teach English pronunciation pedagogy to L2 learners, either via online only or blended on-campus. Thirteen student teachers (five asynchronous online-only and eight blended on-campus) participated in the study. Data sources included: responses to online quizzes assessing student-teachers’ knowledge of English pronunciation; their final assignments; Moodle discussion forum postings; Moodle participation analytics; and narrative frames comprising participants’ accounts of their personal experiences in learning course content. Overall, findings indicated that the student teachers’ knowledge and understanding of how to teach L2 pronunciation was enhanced regardless of which mode of delivery they took. Findings further showed that the Moodle books played a particularly important role for both groups of students in learning course content.